Redefining Tacit Knowledge in Music Performance Evaluation : Preparing Perceptually-Aware Music Leaders : Final Report. - Mitchell, Helen (Office for Learning and Teaching, 2016)
Tertiary music students learn traditional performance skills for the music profession but do not learn to think critically about sound evaluation. Music assessors are not as well prepared to assess sound as they imagine, have limited vocabulary to describe what they hear and are influenced by visual and extra-musical aspects of performances. Traditional music training must incorporate perceptual and cognitive research into effective training programs for future music leaders. This action research project enabled music students to experience the complexities and pitfalls of performance evaluation, to learn from music industry experts and develop training strategies to advance their listening acuity for performance and performer evaluation. The results of this study informed future curricula design to prepare future generations of music leaders to challenge tacit knowledge in the music domain. It prepared tertiary music students to think beyond the craft of music performance, and to create and demand more robust creative assessments.